985 Prevention of common mental disorders in employees – attitudes of health care professionals, human resources managers, and employees in germany. (24th April 2018) - Rieger, MA; Burgess, S; Junne, F; Rothermund, E; Gündel, H; Zipfel, S; Michaelis, M
Abstract : Introduction: Many studies investigate the possible positive and negative effects of work-related factors on mental health of employees, but only little is known about the attitudes of the persons involved. Therefore we aimed to assess the perceptions of occupational health physicians (OHP), primary care physicians (PCP), psychotherapists (PT), human resources managers (HRM), and employees (EMP) with regard to work-related risk factors and possibilities for prevention of common mental disorders (CMD) at the workplace. Methods: A standardised questionnaire was developed to assess the individuals´ attitudes with regard to different aspects of prevention of CMD in employees. The survey assessing the estimates concerning work-related and individual risk factors, cooperation of persons involved, and engagement of specific institutions first was developed for a postal survey among OHPs, PCPs, PTs, and HRMs in 2014. 1 Second, the content was slightly adapted to perform an online survey among employees addressing an online access panel in 2016. Besides descriptive measures or explorative bivariate methods, multivariate logistic regression analysis with IBM SPSS 22 was computed. Results: Data were gathered from 133 OHPs (response rate 30%), 136 PCPs (14%), 186 PTs (27%), 172 HRMs (12%) and 610 EMPs (stipulated number of participants). The significance of several work-related factors (e.g. work-related demands, work organisation) for the development of CMD in employees was judged rather similarly by the health professionals but lower by HRM. The employees´ perception often led between both. Individual predisposition for CMD was rated less important by HRM and EMP than by health professionals. The potential of work-related aspects for prevention of CMD was assess similarly high by health professionals and EMP, but slightly lower by HRM. Discussion: The multiperspective survey revealed different answering patterns of the five groups indicating possibilities as well as need for further actions with regard to work-related prevention of CMD in employees. Reference: . Michaelis, et al. Mental Health & Prevention 2016;4:88–95.